Combined impact of HLA-allele matching and the CD34-positive cell dose on optimal unit selection for single-unit cord blood transplantation in adults. Issue 11 (19th September 2021) - Yabe, Toshio; Satake, Masahiro; Odajima, Takeshi; Watanabe-Okochi, Naoko; Azuma, Fumihiro; Kashiwase, Koichi; Matsumoto, Kayoko; Orihara, Takeshi; Yabe, Hiromasa; Kato, Shunichi; Kato, Koji; Kai, Shunro; et al.
Abstract: The combined effects of HLA-allele matching at six-loci (HLA-A, -B, -C, -DRB1, -DQB1, and -DPB1) and CD34 + cell dose on clinical outcomes were analyzed in 1, 226 adult cases with single-unit unrelated cord blood transplantation. In the six-loci analysis, low HLA-allele matches did not significantly increase the overall mortality compared to higher matches, whereas in the five-loci analysis excluding HLA-DPB1, they caused a higher overall mortality (HR 1.42, p = .002), possibly due to the graft-versus-leukemia effect of HLA-DPB1 mismatches. A lower CD34 + cell dose (<.50 × 10 5 /kg) resulted in higher mortality and lower engraftment; these inferior outcomes were offset by high HLA-allele matches (7-10/10 match), while the inferior outcomes of low HLA-allele matches were improved by increasing the CD34 + cell dose. Consideration of the combined effects of the CD34 + cell dose and HLA matching may expand the options for transplantable units when HLA matching or the CD34 + cell dose is inadequate.